Algorithms for Access Localization to Objects of Scalable Concurrent Pools Based on Diffracting Trees in Multicore Computer Systems - Anenkov, Alexandr D.; Paznikov, Alexey A.; Kurnosov, Mikhail G. (International Conference on Actual Problems of Electronic Instrument Engineering proceedings, 2018)
This work proposes the implementation of scalable concurrent pool based on diffraction trees. Developed pool ensures localization of addresses to shared variables to maximize its throughput. The proposed approaches increase the throughput at high and low workload and provides acceptable level of FIFO/LIFO-order of operation execution and is characterized by low latency of tree traversal. We analyze the efficiency of developed pool. The pool provides large scalability of multithreaded programs compared with similar implementation of pool based on diffraction trees. Developed pools may be applied for producer-consumer model implementation in multithreading programs with constant number of active threads and requirements of high throughput of pools and low latency of operations with pools. Implemented data structure scales well for large number of threads and shows the increase of throughput as the number of threads comes near the number of processor cores. Increasing of tree size in the pool does not reduce the pool throughput. Recommendations for using of pool and the experimental results on multicore computer system are represented in the paper.